MANUSIA DAN HUTAN SUATU KERANGKA FIKIR TRIDHARMA PERGURUAN TINGGI - Ali M.A. Rachman (Media Konservasi, 2006)
This paper is an effort to invite and to review that man-forest as a unity, no separation each other since ancient history about 10.000 years ago. Its theoretical background be based on energy and sociocultural evolution as a tool for understanding growth in global process today. The rising question is to remark in this paper to be answered in mind of review at curriculum Forestry Faculty: “Has it in a set with man-forest as a unity, so far”? The answer of this question is the way to find out in order to go right tract of education, research and community service form of Tri dharma in dinamic change of global process.Key words : Energy Utilization, “U”shape curve, Motivation, Cognition, Limitation, Coevolution